Missed Opportunities For Immunization In Children And Pregnant Women - Benjamin A I; Vadhera K K; Zachariah P (Wolters Kluwer Medknow Publications, 1990)
The role of immunization in reducing childhood mortality cannot be over-emphasised, yet many opportunities for immunization are missed when children and pregnant women visit a health facility. Reducing missed opportunities is the cheapest way to increase immunization coverage. The present study discusses the extent of the problem of missed opportunities for immunization in children and pregnant women and the factors contributing to the problem, in spatiality and community outreach clinics of Christian Medical College & Hospital, Ludhiana. Recommendations are made regarding ways and means of reducing missed opportunities.